Export Management Information System: Evidence from Willbes Global Purwadadi Inc. - Egin Nuranjani; Santi Purwanti; Mohamad Hairiyanov; Jaja Jaja (LPPM Universitas Islam 45 Bekasi, 2022)
The case study in this research is the export goods data report at Willbess Global Inc. The purpose of this research is to design an information system for managing data on export goods based on a website at Willbess Global Inc.. This can help the process of inputting export goods data. Willbess Global Inc. always strives to improve its business process services, especially in the field of exporting goods with more systematic data processing. The research method used is the Rational Unified Process (RUP) which is a software engineering method developed by collecting various best practices in the software development industry. RUP uses an object oriented concept, with activities that focus on model development using the Unified Model Language (UML). This research has produced information system functions contained in each process of functional requirements such as managing, deleting, and changing information data on export goods data, data on types of transportation equipment used and data for export goods travel documents.